2006
DOI: 10.1037/0022-3514.91.3.423
|View full text |Cite
|
Sign up to set email alerts
|

Resisting persuasion by the skin of one's teeth: The hidden success of resisted persuasive messages.

Abstract: Recent research has suggested that when people resist persuasion they can perceive this resistance and, under specifiable conditions, become more certain of their initial attitudes (e.g., Z. L. Tormala & R. E. Petty, 2002). Within the same metacognitive framework, the present research provides evidence for the opposite phenomenon--that is, when people resist persuasion, they sometimes become less certain of their initial attitudes. Four experiments demonstrate that when people perceive that they have done a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 35 publications
1
66
0
Order By: Relevance
“…Participants would therefore be required to exert some cognitive effort to integrate the information into a coherent attitude (cf. Tormala et al, 2006). In experiment 2, it was found that the presentation of risk information always increased risk perceptions, whilst presentation of benefit information did not always increase benefit perception.…”
Section: Discussion Of Experimentsmentioning
confidence: 89%
See 1 more Smart Citation
“…Participants would therefore be required to exert some cognitive effort to integrate the information into a coherent attitude (cf. Tormala et al, 2006). In experiment 2, it was found that the presentation of risk information always increased risk perceptions, whilst presentation of benefit information did not always increase benefit perception.…”
Section: Discussion Of Experimentsmentioning
confidence: 89%
“…However, the results of experiment 1 were interpreted as implying that an attitude or affect heuristic is being created or activated by the information presented first. The information presented last is thus counter-attitudinal; which may influence further processing of information, in particular if the further information is provided involuntary (e.g., Tormala, Clarkson, & Petty, 2006;Tormala & Petty, 2002;Tormala & Petty, 2004). A repeated measures ANOVA with familiarity as a within participant factor and order of information/question (risk/benefit) and provision of information (yes/no) used as between participant factors, was applied.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, perceiving situational change is noteworthy, but this perception of change might be most likely to translate into reduced certainty when it is perceived to have occurred in response to a weak message. Indeed, changing one's attitude in response to a weak attack is more diagnostic of the initial attitude's invalidity than is changing in response to a strong message (Tormala et al, 2006; see also Rucker & Petty, 2004).…”
Section: Studymentioning
confidence: 97%
“…Recent work suggests that when people receive persuasive messages, they can appraise their own message responses (e.g., persuasion or resistance) with implications for attitude certainty (see . This work has revealed that when people positively (negatively) evaluate their own persuasion or resistance, they become more (less) certain of their attitudes (e.g., Rucker & Petty, 2004;Tormala, Clarkson, & Petty, 2006;Tormala, DeSensi, & Petty, 2007). Message response similarity effects would suggest that people's metacognitive assessments in persuasion situations target not only their own message responses, but also the responses of others.…”
Section: Beyond Attitude Consensusmentioning
confidence: 94%